Strategies for public management in the face of society's new challenges (Legal journal - Research in Legal and Social Sciences, 2021)
This articles contains a constitutional analysis of rights and guarantees that are frequently invoked by society, at national or international level, individually orcollectively, to demand access to public information about the use of funds pertaining to the General Budget of the Nation and other public funds. With respect to the field of justice, the demand is to access to the status of the complaints that were made by media, organizations, town councillors etc., related to unlawful public management. For the perpetration of these acts, the intervention of public servants was necessary. These corruption cases became more visible with the public complaints and with the conviction of public officials. These circumstances require special analysis and strategies, for a high percent of the population works for the State, which emphasizes the need for comprehensive training in values, ethic, and cooperation at national and international level. This investigation was possible thank to bibliographical andopen sources, and to get to the conclusion, the observation was applied as technic. With the results of this study, several tools and strategies are proposed, in order to get back citizens' trust and also to achieve institutional empowerment.
Keywords: cooperation; training; human talent; estrategy; corruption; public management